Using Landsat-8 Imagery Data on Mapping of The Seagrass Distribution in Matahari Island, Pulau Banyak District, Aceh Province, Indonesia - Syahrul Purnawan; Fauzan Aulia; Teuku Khairuman (Aceh International Journal of Science and Technology, 2016)
The objective of the present study was to gathers information about the seagrass distribution area using the remote sensing that retrieved from Landsat-8. Analysis of Landsat-8 image is classified into 6 classes; seagrass, coral reefs, sand, sea, and cloud. The agreement between processed image of seagrass bed and ground truth reference was 70%. The seagrass ecosystem is well distributed along the Matahari Island, with the total area approximately 44.0123 Ha.